Curva diaria de presión intraocular en pacientes atendidos en el Centro Ofatamológico y en el Hospital Manuel Ygnacio Montero en el periodo enero-junio del 2014 - Carrión Jaramillo, Michael Alejandro (2015)
The daily pressure curve is a semiological process that provides diagnostic data, it is an aid in the therapeutic evaluation and in some cases provides prognostic information in patients suffering from glaucoma - it is based on measuring the eye pressure with different tonometers at different times in 24 hours day - the elevation of intraocular pressure (IOP) above a critical level earned individually is the main cause of damage to the ganglion cells of the optic nerve, that is why this research was conducted denominated: DAILY CURVE INTRAOCULAR PRESSURE IN PATIENTS TREATED IN HOSPITAL YGNACIO MANUEL MONTERO(IESS) AND the EYE CLINIC IN THE PERIOD JANUARY - JUNE 2014. The main objective of this research was to determine the variations of intraocular pressure in patients treated at the Hospital Centroftalmologico and Manuel Ignacio Montero. The methodology is a prospective descriptive sectional study of patients admitted to hospital Manuel Ygnacio Montero and the EYE CLINIC consisted of indentation tonometry Schiotz with tonometer at different times of day (6 am,9am,12pm,3pm,6pm , 10pm). Conducting the study to a total of 81 pa-patients (162 eyes) se obtained a variation in IOP and Found 20.6 mmHg and 13.4 as normal lower limit mmHg; in addition it was found that the IOP is higher in patients of older ages; It states that there is greater variability of IOP in females; It is determined as a IOP average value of 17.34 mmHg in the population of loja. Key words: Glaucoma; Intraocular pressure (P.I.O); Schiotz tonometer; gangli-on cells.